世界毒品问题报告 2017 - United Nations (United Nations, 2017)
This report includes an updated overview of recent trends on production, trafficking and consumption of key illicit drugs as well as highlighting a thematic area of concern. It maintains a global overview of the baseline data and estimates on drug demand and supply and provides a reference point on the drug situation worldwide. The thematic focus of the 2017 edition is on the links that exist between drugs, terrorism, corruption, transnational organized crime and illicit financial flows.